One-pot fabrication of triple shape memory hydrogel based on coordination bond, the dynamic borate ester bonds, and hydrogen bond. Issue 4 (2nd October 2019) - Wang, Minying; Wang, Ling; Xu, Yuande; Fu, Lihua; Yang, Hua
ABSTRACT: In order to achieve the application of shape memory hydrogel (SMH), the hydrogel must be simple in design, adjustable in mechanical properties, and easy to achieve in shape memory properties. In the article, triple SMHs were fabricated by simple method with adjustable mechanical properties. The triple SMH including coordination bond between sodium alginate and Fe 3+, the dynamic borate ester bonds, and hydrogen bond of poly (vinyl alcohol) (PVA) were designed to memorize temporary shapes.